The Iron Boost: A Nutritional Snack with Lepidium Sativum and Oryza Sativa - Sharma Priya; Mishra Priya (BIO Web of Conferences)
Anaemia occurs when tissues cannot maintain a normal haemoglobin concentration, Lepidium sativum is rich in protein, fatty acid, vitamin, minerals, and various bioactive compounds. Combined with rice flakes flour, jaggery and dry fruits they serve as an excellent iron source. This study aims to develop and standardize snacks using these ingredients and to assess the sensory characteristics. The study was conducted to develop a product from garden cress seeds and rice flake flour, jaggery and dry fruits. Garden cress seeds and rice flakes were dry roasted and churned into a fine powder and combined into a dough using remaining ingredients. Sticks were made with the help of a Sev making machine and baked in the oven. Formulation of sticks and the optimization of the product based on sensory properties. For sensory evaluation, the product was used in different variations. In T1- garden cress seeds (2og), rice flour (50g), jaggery (20g), almonds (2.5g), raisins (2.5g). In T2, garden cress seeds (25g), rice flour (50g), jaggery (20g), almonds (2.5g), raisins (2.5g), respectively. The sensory evaluation was done by using a 9-point hedonic scale. The study revealed that T2 was the most acceptable product in various parameters. This study concluded that sample T2 can be used for anaemic population as it’s nutritional composition after testing included 9.83g moisture, 2.97g ash, 7.5g protein, 5.8g fibre, 11.2g fat, 13.6mg iron. It improves bioavailability, aids in public health initiatives, and offers sustainable, natural alternatives to synthetic supplements